1999
DOI: 10.1111/j.1471-0528.1999.tb08326.x
|View full text |Cite
|
Sign up to set email alerts
|

Twin mothers, pregnancy hypertension and pre‐eclampsia

Abstract: Objective To estimate the maternal genetic contribution to the hypertensive diseases of pregnancy.Design A cohort study of female twins with information on hypertensive diseases of pregnancy obtained by questionnaire screening, and verification of diagnosis from hospital or general practitioner records.Setting A volunteer twin registry in the UK with recruitment through the media without reference to pregnancies or disease status.Population Adult female, same-sex twin pairs who completed a pregnancy history qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 35 publications
2
31
0
2
Order By: Relevance
“…A number of studies have described a strong familial trend to developing HDP Chesley et al 1968;Chesley and Cooper 1986;Salonen Ros et al 2000), and recently a heritability estimate of 0.47 was observed for HDP in a large sample of over 2,000 twin pairs of women, indicating that HDP, both with proteinuria (PE) and without proteinuria (GH), is highly heritable (Salonen Ros et al 2000). Published data suggest a significant genetic component to HDP, which may include fetal and environmental factors (Broughton Pipkin 2001;Chesley and Cooper 1986;Cooper 1993;GOPEC Consortium 2005;Roberts and Cooper 2001;Salonen Ros et al 2000; Thornton and Macdonald 1999). Finally, it is still debated whether PE and GH represent different manifestations of the same entity or rather distinct pathogenic disorders (Brown et al 2001;Fisher et al 1981;Seely and Solomon 2003;Vatten and Skjaerven 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have described a strong familial trend to developing HDP Chesley et al 1968;Chesley and Cooper 1986;Salonen Ros et al 2000), and recently a heritability estimate of 0.47 was observed for HDP in a large sample of over 2,000 twin pairs of women, indicating that HDP, both with proteinuria (PE) and without proteinuria (GH), is highly heritable (Salonen Ros et al 2000). Published data suggest a significant genetic component to HDP, which may include fetal and environmental factors (Broughton Pipkin 2001;Chesley and Cooper 1986;Cooper 1993;GOPEC Consortium 2005;Roberts and Cooper 2001;Salonen Ros et al 2000; Thornton and Macdonald 1999). Finally, it is still debated whether PE and GH represent different manifestations of the same entity or rather distinct pathogenic disorders (Brown et al 2001;Fisher et al 1981;Seely and Solomon 2003;Vatten and Skjaerven 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence suggesting that HDP are multifactorial (Roberts and Cooper 2001;Talosi et al 2000; Thornton and Macdonald 1999), but the etiology and mechanisms causing PE and GH are still undefined. Current pathophysiological hypotheses imply inade-quate trophoblastic invasion, oxidative stress, endothelial dysfunction, inappropriate maternal immunological response and genetic susceptibility (Dekker and Sibai 1998;Roberts and Cooper 2001;Sibai et al 2005;Solomon and Seely 2001;Talosi et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported familial aggregation of pre-eclampsia, which suggests that genetic factors contribute to the pathogenesis of this disease (Morgan and Ward, 1999). Genetic factors account for 25 to 55% of the risk of developing pre-eclampsia (Thornton and Macdonald, 1999;Salonen Ros et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Además, esto se demuestra por las altas tasas de concordancia entre gemelas monocigóticas, comparadas con las dicigóticas (11)(12)(13). Sin embargo, el hecho de que también se hayan observado gemelas discordantes sugiere que el fenotipo fetal, al igual que los factores ambientales, pueden ser importantes en la susceptibilidad a la preeclampsia (14,15).…”
unclassified